2017
DOI: 10.1377/hlthaff.2017.0135
|View full text |Cite
|
Sign up to set email alerts
|

Mortality In Rural China Declined As Health Insurance Coverage Increased, But No Evidence The Two Are Linked

Abstract: Health insurance holds the promise of improving population health and survival and protecting people from catastrophic health spending. Yet evidence from lower- and middle-income countries on the impact of health insurance is limited. We investigated whether insurance expansion reduced adult mortality in rural China, taking advantage of differences across Chinese counties in the timing of the introduction of the New Cooperative Medical Scheme (NCMS). We assembled and analyzed newly collected data on NCMS imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Evidence on health insurance and mortality in middle-and low-income countries is limited [7]. Some retrospective cohort studies conducted in China showed that uninsured people have higher mortality than insured people [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on health insurance and mortality in middle-and low-income countries is limited [7]. Some retrospective cohort studies conducted in China showed that uninsured people have higher mortality than insured people [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Private coverage has been demonstrated as being associated with lower all-cause mortality [3,6]. Additionally, one recent study also showed that publicly-financed health spending was associated with lower mortality rates in middle-income and low-income countries [7]. However, few studies evaluate the association of private coverage with cardiovascular disease (CVD), cancer and other cause-specific mortalities, including mortality from Alzheimer's disease, kidney disease, influenza and pneumonia and chronic lower respiratory disease (CLRD).…”
Section: Introductionmentioning
confidence: 99%
“…This is a government-run, voluntary, county-based and cost-sharing medical insurance program, which aims to improve access to healthcare services for rural residents (15). By 2012, the NCMS had become available to almost all residents in rural China (16).…”
Section: Introductionmentioning
confidence: 99%
“…A series of quasi-experimental studies assessing the health consequences of the scheme also produced mixed results [7,19,20,21]. Using data from twenty-two provinces, the scheme was estimated to be associated with a 9.4% reduction in three-year mortality among seniors in the eastern region [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the sample as a whole, changes in mortality rates were more modest (3.7%) [20]. The most recent study, using nationally representative data from the Disease Surveillance Point system of the Chinese Center for Disease Control and Prevention, found no statistically significant correlation between the implementation of NCMS and reductions in mortality [21]. However, the large standard errors of the estimated NCMS coefficients indicate that it is still possible the scheme had a positive effect on mortality.…”
Section: Introductionmentioning
confidence: 99%